Answers

The Brainliest Answer!
2014-09-01T19:26:02+05:30

the general formula is
a^3+-b^3=(a+-b)(a^2-+ab+b^2)

in our case will be
a^3+b^3=(a+b)(a^2-ab+b^2)

till now we know only a+b=10 and ab=21

So we have
10(a^2+b^2-21)=

We need to find out a^2+b^2

but a+b=10 /()^2=
a^2+2ab+b^2=100
a^2+2*21+b^2=100
a^2+b^2=100-42
a^2+b^2=58

so
10(58-21)=
10*37=370
1 5 1
2014-09-01T19:41:37+05:30
A+b=10
ab=21
a=21/b
21/b+b=10
(21+b ^{2})/b=10
21+b ^{2} =10b
  b ^{2} -10b+21=0
  b ^{2} -3b-7b+21=0
  b(b-3)-7(b-3)=0
  b=3,7
  substitute b=3,7 in ab=21   3a=21
  a=7
  when b=3 then a=7
  7a=21
  a=3
  when b=7 then a=3
so,a^{3} +b^{3}    =7^{3} +3^{3} or 3^{3}+7^{3}   =343+27 or 27 +343   =370
0